Specific incremental test in elite squash players. Issue 12 (23rd November 2005) - Girard, O; Sciberras, P; Habrard, M; Hot, P; Chevalier, R; Millet, G P
Abstract : Objectives: To compare cardiorespiratory responses between incremental treadmill (non-specific) and field (sport specific) tests in elite squash players. Methods: Seven elite players (ranked 1 to 25 in their national federation including the World number 1) randomly performed an incremental treadmill test (TT) and a squash specific graded test (ST) to exhaustion. The ST consisted of repeated displacements replicating the game of squash, at increasing speed on the court. In both tests, ventilatory variables and heart rate were determined at the ventilatory threshold, respiratory compensation point, and maximal loads (max). Results: Heart rate and percentage maximal oxygen uptake (V˙o 2 max ) at the ventilatory threshold and respiratory compensation point were not different between the ST and TT, whereas V˙o 2 max was higher in the ST than in the TT (63.6 (3.0) v 54.9 (2.5) ml/kg/min; p<0.001). Time to exhaustion was not different between the ST and TT (1056 (180) v 962 (71) seconds) but correlated with the ranking of the players only in the ST ( r  =  −0.96, p<0.001). Conclusions: V˙o 2 max values derived from laboratory testing were not relevant for accurately estimating fitness in elite squash players. So the ST may be used as an additional test for determination of training intensity. Improved training advice for prescribing aerobic exercise or perfecting stroke technique may result from these results.